Semana de manifestações culturais: promovendo espaços de transformação - Gambarini, Alana Pinto Coelho [UNESP]; Aragão, José Euzébio de Oliveira Souza [UNESP]; Marucci, Stephanie [UNESP]; Castro, Júlia Astelli [UNESP]; Pereira, Andressa Braw Brito [UNESP]; Matias, Maria Magali [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The event “Semana de Manifestações Culturais” (Week of Cultural Manifestations) is held annually by the project of Brazilian Dances and Rhythms of the University UNESP / Rio Claro. The merit of the project is diving in popular culture, going beyond the formal research. The energy that sustains our project comes from music and dance, elements that produce an immediate interaction with others, where learners also teaches, and vice versa. In our activities, we seek to remain true to the traditions, but also we enable new regards and languages, because culture has this aspect of freedom and creation. The Week of Cultural Events arose from the desire and need of the students to disclose, to a wider audience, the work done by the project throughout the year and deepen some discussions. This is attended by inviting guests involved in the subject, as masters of popular culture and researchers. The Week is always open to everyone interested. Each year, the week provides new knowledges and reflections, directly reaching between 100 and 200 people.

A Semana de Manifestações Culturais é um evento realizado anualmente pelo Projeto de Extensão de Danças e Ritmos Brasileiros da UNESP/Rio Claro. O mérito do projeto é o mergulho na cultura popular, que ultrapassa a pesquisa formal. A energia que nos mantém vem da música e da dança, elementos que produzem uma imediata interação com o público, onde quem aprende também ensina, e vice-versa. Em nossas atividades, buscamos manter-nos fiéis às tradições, mas também possibilitamos novos olhares e linguagens, pois a cultura possui este aspecto de liberdade e recriação. A Semana de Manifestações Culturais surgiu do desejo e necessidade dos alunos em divulgar, para um público mais amplo, o trabalho realizado pelo projeto ao longo do ano e aprofundar algumas discussões, com a presença de convidados mais envolvidos no assunto, como mestres da cultura popular e pesquisadores do tema. A Semana é sempre aberta a todas as pessoas interessadas. A cada ano, a Semana proporciona novos conhecimentos e reflexões, atingindo diretamente entre 100 e 200 pessoas.
Keywords: Cultural manifestations; Brazilian dances and rhythms; Popular culture; Extension; University; Manifestações culturais; Danças e ritmos brasileiros; Cultura popular; Extensão; Universidade